2002
DOI: 10.1128/aem.68.9.4201-4208.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Sinorhizobium meliloti Strain with a Modified putA Gene on the Rhizosphere Microbial Community of Alfalfa

Abstract: The success of a rhizobial inoculant in the soil depends to a large extent on its capacity to compete against indigenous strains. M403, a Sinorhizobium meliloti strain with enhanced competitiveness for nodule occupancy, was recently constructed by introducing a plasmid containing an extra copy of a modified putA (proline dehydrogenase) gene. This strain and M401, a control strain carrying the same plasmid without the modified gene, were used as soil inoculants for alfalfa in a contained field release experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Similar results were obtained in other culture dependent (Walsh et al, 2001) and cultureindependent (Van Dillewijn et al, 2002;Viebahn et al, 2003) studies after the introduction of genetically modified bacteria on various plants. In these studies, seasonal shifts of community composition, but only minor, transient shifts due to the beneficial microorganisms, were detected.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained in other culture dependent (Walsh et al, 2001) and cultureindependent (Van Dillewijn et al, 2002;Viebahn et al, 2003) studies after the introduction of genetically modified bacteria on various plants. In these studies, seasonal shifts of community composition, but only minor, transient shifts due to the beneficial microorganisms, were detected.…”
Section: Discussionsupporting
confidence: 90%
“…In S. meliloti, a DputA strain has a weakened ability to form root colonies [35] and, moreover, strains complemented with additional copies of putA are more competitive at establishing a symbiotic relationship with alfalfa [36,37]. The Put system has also been linked to infectivity in both Helicobacter hepaticas and Helicobacter pylori [28,29,38], and the Put system plays a role in regulating the cell cycle within Ehrlichia chaffeensis [39].…”
Section: Discussionmentioning
confidence: 99%
“…DGGE has been employed to investigate the microbial communities within the different plant rhizospheres and to monitor the effects of microbial inoculants on the rhizosphere communities. van Dillewijn et al (2002) determined the effect of Sinorhizobium meliloti on the rhizosphere microbial community of its host plant, alfafa (Medicago sativa), and found that the plant appeared to have a much stronger influence on the microbial community compared with a S. meliloti inoculation. Schwieger and Tebbe (2000) studied the impact of rhizobial inoculant, S. meliloti L33, on the microbial communities of M. sativa rhizosphere and found that both plant species and inoculant had an effect on the rhizosphere structure.…”
Section: Introductionmentioning
confidence: 99%